Preventive Effects of Taurine on Development of Hepatic Steatosis Induced by a High-Fat/Cholesterol Dietary Habit - Chang, Yuan-Yen; Chou, Chung-Hsi; Chiu, Chih-Hsien; Yang, Kuo-Tai; Lin, Yi-Ling; Weng, Wei-Lien; Chen, Yi-Chen (Journal of agricultural and food chemistry, 2011)
Nonalcoholic fatty liver (NAFL) is also called hepatic steatosis and has become an emergent liver disease in developed and developing nations. This study was to exam the preventive effects of taurine (Tau) on the development of hepatic steatosis via a hamster model. Although hepatic steatosis of hamsters was induced by feeding a high-fat/cholesterol diet, drinking water containing 0.35 and 0.7% Tau improved (p < 0.05) the serum lipid profile. Meanwhile, the smaller (p < 0.05) liver sizes and lower (p < 0.05) hepatic lipids in high-fat/cholesterol dietary hamsters drinking Tau may be partially due to higher (p < 0.05) fecal cholesterol, triacylglycerol, and bile acid outputs. In the regulation of lipid homeostasis, drinking a Tau solution upregulated (p < 0.05) low-density lipoprotein receptor and CYP7A1 gene expressions in high-fat/cholesterol dietary hamsters, which result in increased fecal cholesterol and bile acid outputs. Drinking a Tau solution also upregulated (p < 0.05) peroxisome proliferator-activated receptor-α (PPAR-α) and uncoupling protein 2 (UPC2) gene expressions in high-fat/cholesterol dietary hamsters, thus increasing energy expenditure. Besides, Tau also enhanced (p < 0.05) liver antioxidant capacities (GSH, TEAC, SOD, and CAT) and decreased (p < 0.05) lipid peroxidation (MDA), which alleviated liver damage in the high-fat/cholesterol dietary hamsters. Therefore, Tau shows preventive effects on the development of hepatic steatosis induced by a high-fat/cholesterol dietary habit.